Pengembangan Kemampuan Kognitif melalui Game Gambar dan Huruf Serasi Studi Kasus di Sekolah RA Bunayya Bin Baz Yogyakarta - Wiresti, Ririn Dwi Wiresti; Hilalludin, Hilalludin (Jurnal I TIBAR, 2025)
Cognitive development is a crucial aspect of early childhood growth, where children are stimulated to develop thinking skills and problem-solving abilities. However, in practice, learning methods often lack engagement and do not align with the characteristics of young children. Boring learning approaches can hinder children's interest in recognizing letters and reading. Therefore, an innovative strategy is needed to make learning more enjoyable and effective. This study aims to enhance early childhood cognitive development through the Gambar dan Huruf Serasi (Harmonious Picture and Letter) game. The research employs a qualitative method with a case study approach. The subjects of this study are 17 children aged 5–6 years at RA Bunayya Bin Baz Yogyakarta. To ensure data credibility, source triangulation was used by involving observations, interviews, and documentation. The findings indicate that the Gambar dan Huruf Serasi game positively impacts children's cognitive development. This game has been proven to: (1) increase children's reading interest, (2) enhance interest in learning letters and reading, (3) stimulate children's memory, and (4) enrich their vocabulary. Based on these findings, it can be concluded that implementing educational games based on pictures and letters significantly improves children's cognitive abilities while making learning more enjoyable and effective for early childhood education.